2014
DOI: 10.5530/pj.2014.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Beetroot Extract against Phenyl Hydrazine Induced Anemia in Rats

Abstract: Background: Anemia can be regarded as one of the oldest blood malformation known over a century. Megaloblastic anemia arises due to curtailed formation of erythrocytes, which leads to formation of a large number of underdeveloped erythrocytes. Proper nutritional supplementation may be useful in such condition. Beta vulgaris or beetroot is one of the important vegetables consumed worldwide. The aim of the present work was to evaluate anti-anemic potential of beetroot. Methods: Beetroot was extracted with ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…B 12 and folic acid in the beetroot leaf which could be reversed the effects of phenylhydrazine drug. These results are agreements with vitamin and minerals found in beetroot are most likely active ingredients responsible for its hematinic effects [45]. On the other hand, the highest significant increases of RBC count, HGB concentration and HCT percentage showed in group II compared with control group at D21 and D42 days.…”
Section: Hematological Parameterssupporting
confidence: 88%
“…B 12 and folic acid in the beetroot leaf which could be reversed the effects of phenylhydrazine drug. These results are agreements with vitamin and minerals found in beetroot are most likely active ingredients responsible for its hematinic effects [45]. On the other hand, the highest significant increases of RBC count, HGB concentration and HCT percentage showed in group II compared with control group at D21 and D42 days.…”
Section: Hematological Parameterssupporting
confidence: 88%
“…For instance, Jaiswal et al (25) showed that treatment of anemic rats with extracts of the plant root prepared by hot percolation in a Soxhlet apparatus significantly reversed the decrements of RBCs count and HGB concentration. More recently, Al-aboud (26) found that taking eight grams of beetroot for 20 days by female volunteers resulted in mild increase in hemoglobin, ferritin, and serum iron levels.…”
Section: Discussionmentioning
confidence: 99%
“…Normal red cell production requires diet containing protein, iron, copper, vitamin B 2 , B 6 , B 12 and folic acid (Nyaulingo, 2013). The study done by Jaiswal et al, (2014) reported that administration of 200 mg/kg beetroot extract to phenyl hydrazine-induced anemic rats significantly increased (p < 0.01) the number of RBCs as well as hemoglobin concentration when compared to the untreated group. Beetroot was found to be rich in folic acid, ascorbic acid, iron, vitamin and minerals which are most likely active ingredients responsible for its haematinic effects.…”
Section: Discussionmentioning
confidence: 95%